The Big Gamble The Migration of Eritreans to Europe - Belloni, Milena (University of California Press, 2019)
Tens of thousands of Eritreans make perilous voyages across Africa and the Mediterranean Sea every year. Why do they risk their lives to reach European countries where so many more hardships await them? By visiting family homes in Eritrea and living with refugees in camps and urban peripheries across Ethiopia, Sudan, and Italy, Milena Belloni untangles the reasons behind one of the most under-researched refugee populations today. Balancing encounters with refugees and their families, smugglers, and visa officers, The Big Gamble contributes to ongoing debates about blurred boundaries between forced and voluntary migration, the complications of transnational marriages, the social matrix of smuggling, and the role of family expectations, emotions, and values in migrants' choices of destinations. "Milena Belloni's engrossing ethnography-carried out across time, space, and place- is particularly commendable because of her scholarly commitment to 'getting things right.' The Eritrean women and men whose lives provided its empirical ground will see their pain, joy, and contradictions reflected back at them. This is scholar activism at its finest." LAURA BISAILLON, Professor of Health and Society, University of Toronto Scarborough "The Big Gamble is a study of a migrant group that has received very little scholarly attention. Its focus on the Eritrea to Europe corridor is a novel approach, and Milena Belloni has produced a compelling and courageous account." PETER KIVISTO, Augustana College and University of Helsinki "A monumental and perceptive story of migration, taking the reader on a journey not just from Africa to Europe but through reflections on moralities, risk, and trust that are central to contemporary mobility and immobility. Belloni's account of Eritrean migration experiences is powered by formidable fieldwork and written with warmth and wisdom." JØRGEN CARLING, Peace Research Institute Oslo MILENA BELLONI is a sociologist at the University of Trento. Her doctoral research on Eritrean migration received the 2016 IMISCOE Award. Belloni has published in the Journal of Refugee Studies and the Journal of Ethnic and Migration Studies.